Prolongations of Golden Structure to Bundles of Infinitely Near Points - Georges Florian Wankap Nono; Achille Ntyam; Emmanuel Hinamari Mang-Massou (IndoMS, 2022)
For a Golden-structure ζ on a smooth manifold M and any covariant functor which assigns to M its bundle MA of infinitely near points of A-king, we define the Golden structure ζ^A on M^A and prove that ζ is integrable if and only if so is ζ^A. We also investigate the integrability, parallelism, half parallelism and anti-half parallelism of the Golden-structure ζ^A and their associated distributions on M^A.